The Relationship Between MGNREGA and Internal Labour Migration in Tamil Nadu, India. Issue 2 (April 2018) - Dodd, Warren; Wyngaarden, Sara; Humphries, Sally; Patel, Kirit; Majowicz, Shannon; Little, Matthew; Dewey, Cate
Abstract India's constitution contains provisions for the 'right to work' and the 'right to movement' for all citizens. Established in 2005, the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is broadly considered to operationalize this 'right to work'. At the same time, a public discourse persists that views MGNREGA as a substitute for internal labour migration. Drawing on the results from 300 household surveys in threepanchayats in the Krishnagiri district of Tamil Nadu, we test the validity of this discourse in this setting. We find that households that rely exclusively on MGNREGA have different demographic and socioeconomic characteristics compared to households that rely exclusively on remittances from internal labour migration. Furthermore, 20 per cent of households surveyed use both MGNREGA and internal labour migration as complementary livelihood strategies. We argue that there is a need for better understanding and recognition of the complementary potential of MGNREGA and internal labour migration. La constitution de l'Inde contient des dispositions pour le «droit au travail» et le «droit de circuler» pour tous les citoyens. Créée en 2005, la loi nationale Mahatma Gandhi de garantie de l'emploi en milieu rural (MGNREGA) est largement considérée comme rendant opérationnel ce «droit au travail» . Dans le même temps, un discours public persistant considère la loi MGNREGA comme un substitut à la migration interne de main-d'œuvre. Sur la base des résultats de 300 enquêtes auprès des ménages dans trois panchayats du district de Krishnagiri au Tamil Nadu, nous testons la validité de ce discours dans ce contexte. Nous constatons que les ménages qui dépendent exclusivement de la loi MGNREGA ont des caractéristiques démographiques et socioéconomiques différentes de celles des ménages qui dépendent exclusivement des envois de fonds provenant de la migration interne de la main-d'œuvre. En outre, 20% des ménages interrogés utilisent à la fois la loi MGNREGA et la migration interne de main-d'œuvre comme stratégies de subsistance complémentaires. Nous soutenons qu'il est nécessaire de mieux comprendre et de reconnaître le potentiel de complémentarité de la loi MGNREGA et de la migration interne de main-d'œuvre.